Carbon nitride homojunction photocatalyst containing amidoxime group and nitrogen defect as well as preparation method and application of carbon nitride homojunction photocatalyst
By modified the carbon nitride front -drive body through the high temperature melt and high temperature alkali etching method, and the heat aggregation of the high -temperature burn method, prepare the nitrogen -nitride homogeneous catalyst containing pyride groups and nitrogen defects It solves the problem of being difficult to coordinate with adsorption and high -efficiency photocatalytic reduction of uranium root ions, and realize the efficient removal and fixation of uranium pollution in wastewater.
Patent Information
- Application Number
- CN202411643382.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
AI Technical Summary
It is difficult to develop a catalyst that can coordinate the adsorption of uranyl root ions (U(VI)) and efficient photocatalytic reduction of uranyl root ions for efficient fixed removal of uranium pollution in wastewater.
Through the high -temperature melting method and the high temperature alkali etching method, the carbon nitride (CNX) of nitrogen -containing defects (CNX) with nitrogen -containing defects is obtained through the high -temperature melting method and high -temperature alkali etching method, and then the heat occurs between the two through the simple high temperature burn method. Polytes, carbonate -nitride homogenous co -catalysts (CNX/ACN) containing pyride groups and nitrogen defects.
This photocatalyst has the characteristics of efficient absorption, rapid capture of U (ⅵ), and high -efficiency photogonic deriven separation, and realize the efficient removal and fixation of uranium pollution in wastewater. It reaches 99.9%, and the materials are stable, the preparation method is simple, and it has certain environmental protection benefits.
Smart Images

Figure CN119346156A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a method for preparing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects, a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects prepared by the preparation method, and application of the photocatalyst in visible light catalytic reduction to remove heavy metals. Background Art
[0002] Energy is the foundation of national economic development. Compared with traditional fossil energy and new energy, nuclear energy is still the most mature technology. Uranium is the most important nuclear material resource. A large amount of uranium wastewater and waste residue will be produced in the process of uranium mining and smelting, uranium enrichment, nuclear power plant operation, and uranium tailings treatment and disposal. The waste residue gradually leaches uranium under long-term weathering and rainwater leaching, migrates and spreads to the surrounding water environment, and increases the output of uranium wastewater. Soluble uranyl ions (U(VI)) are the main form of uranium in surface water. After entering the natural environment, they are accumulated by the human body through the food chain, posing a huge threat to human kidneys, liver, lungs and other organs.
[0003] The photocatalytic reduction and fixation method of U(VI) has the advantages of mild reaction conditions, green friendliness, and low energy consumption, and is regarded as one of the most promising uranium wastewater remediation technologies. In this method, the regulation and development of photocatalysts with excellent performance is the key to promoting U(VI) removal and recovery technology. Among the many U(VI) photocatalysts, graphite-phase carbon nitride (g-C3N4) is a high molecular polymer with a typical graphene-like layered structure. The triazine ring unit structure composed of C and N atoms forms a highly delocalized π-bond conjugated system. g-C3N4 also has the advantages of high temperature tolerance, insolubility in organic solvents, strong chemical stability, and the ability to respond to visible light. At present, the preparation of environmentally friendly, inexpensive, and highly efficient photocatalysts that can absorb light energy and separate electron-hole pairs (e-hole pairs) is being explored. - -h + ), inducing the reduction of U(VI) to fix the g-C3N4-based photocatalyst is the core of the development of this process. The homojunction process of g-C3N4 uses the mutual contact of two similar g-C3N4 to make their band gaps staggered, forming a built-in electric field at the contact surface between the two, thereby improving the photogenerated e - -h + separation efficiency.
[0004] Methods such as morphology control and element doping can effectively change the band structure of g-C3N4, thereby improving the conductivity and carrier lifetime of the material. However, the introduction of other metal elements by doping can induce secondary pollution in the water treatment process and reduce the safety of the composite material. Defect control can effectively change the local microenvironment of the semiconductor surface, which is one of the effective ways to enhance the adsorption performance of photocatalysts and improve their conductivity, redox potential and catalytic activity. Nitrogen defects (N x) can induce an intermediate state gap, efficiently excite the carriers of the light system, and act as a trap center to delay e - -h + The activity of g-C3N4 photocatalytic reduction of U(VI) is also closely related to its surface adsorption performance of U(VI). In order to achieve the efficiency and in-situ regeneration of the photocatalyst, it tends to achieve synergistic U(VI) enrichment, photocatalytic reduction and other reactions in one, give full play to the advantages of adsorption and catalysis, and finally effectively improve the removal performance of U(VI) in wastewater.
[0005] Therefore, how to modify and regulate the physical and chemical properties of g-C3N4 and develop a catalyst that can synergize U(VI) adsorption and efficient photocatalytic reduction with this economical and chemically stable material to achieve efficient fixation and removal of uranium pollution in wastewater is an urgent problem to be solved. Summary of the invention
[0006] In view of this, it is an urgent technical problem to develop a catalyst that can coordinate U(VI) adsorption and efficient photocatalytic reduction to achieve efficient fixed removal of uranium pollution in wastewater. In the first aspect, the present invention provides a method for preparing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects, mainly using carbon nitride as a precursor, and obtaining amidoxime group-modified carbon nitride (ACN) and nitrogen-deficient (N-deficient) carbon nitride by high-temperature molten salt method and high-temperature alkali etching method, respectively. x ) of carbon nitride (CN x ), and then a simple high-temperature calcination method is used to cause thermal polymerization between the two, and finally a amidoxime group and a nitrogen defect (N x ) of carbon nitride homojunction photocatalyst.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects comprises the following steps:
[0009] Step (1), after the carbon nitride precursor and the sodium salt are mixed and ground evenly, the amidoxime group-modified carbon nitride is obtained by a high-temperature molten salt method;
[0010] Step (2), subjecting the carbon nitride precursor to a high temperature alkali etching method to obtain carbon nitride containing nitrogen defects;
[0011] Step (3), the amidoxime group-modified carbon nitride of step (1) and the carbon nitride containing nitrogen defects of step (2) are mixed in a weight ratio of preferably (0.125-1.0):1, more preferably 1:2, and then calcined at high temperature to cause thermal polymerization between the two, and finally obtain a carbon nitride homojunction photocatalyst (CN) containing amidoxime groups and nitrogen defects. x / ACN photocatalyst).
[0012] It should be noted that the above steps (1) and (2) have a certain order of precedence, for example, steps (1) and (2) can be prepared simultaneously, or step (1) or (2) can be performed first, and then step (2) or (1).
[0013] Preferably, step (1) is specifically:
[0014] The carbon nitride precursor and the sodium salt are mixed and ground evenly, placed in a porcelain crucible, calcined at 500-700°C for 1-3 hours, cooled to obtain cyanide-rich carbon nitride, added to water, and then added with hydroxylamine hydrochloride and alkaline substances to obtain a mixed solution, stirred hydrothermally at high temperature, centrifuged and dried to obtain amidoxime group-modified carbon nitride;
[0015] Preferably, the carbon nitride precursor is urea;
[0016] Preferably, the sodium salt is sodium chloride, more preferably, the sodium salt is added in the form of sodium chloride crystals, and most preferably, the mass ratio of sodium chloride to urea is preferably (1.0-5.0):1;
[0017] Preferably, the calcination is carried out in a muffle furnace, more preferably, the temperature is increased to 530° C. at a heating rate of 10° C. / min;
[0018] Preferably, the water level is deionized water, more preferably, the mass ratio of cyanide-rich carbon nitride to deionized water is 1:(50-80), and the mass ratio of cyanide-rich carbon nitride to hydroxylamine hydrochloride is 1:(5.0-8.0);
[0019] Preferably, the alkaline substance is sodium hydroxide, more preferably, the sodium hydroxide is added in the form of solid particles, and most preferably, the concentration of sodium hydroxide in the aqueous solution is preferably 0.03 to 0.1 g / mL;
[0020] Preferably, the high temperature is 70-80°C;
[0021] Preferably, the stirring method is magnetic stirring, and more preferably, the magnetic stirring speed is 200 to 300 rpm;
[0022] Preferably, the centrifugation condition is: centrifugation at a rotation speed of 6000-8000 rpm for 15-20 min.
[0023] Preferably, step (2) is specifically:
[0024] The carbon nitride precursor is dissolved in an alkaline solution, heated and stirred until completely dry, and the mixture is placed in a covered porcelain crucible, calcined at 500-700°C for 2-6 hours, and cooled to obtain carbon nitride containing nitrogen defects;
[0025] Preferably, the carbon nitride precursor is urea, and more preferably, the mass ratio of the carbon nitride precursor to the alkaline substance in the alkaline solution is (1800-2400):1;
[0026] Preferably, the alkaline solution is a KOH solution, and more preferably, the concentration of the alkaline solution is 0.2 to 0.4 g / L;
[0027] Preferably, the stirring method is magnetic stirring, more preferably, the stirring speed is 200 to 300 rpm, and the stirring time is 15 to 20 h;
[0028] Preferably, the heating temperature is 50-70°C;
[0029] Preferably, the calcination is carried out in a muffle furnace, more preferably, the temperature is increased to 520° C. at a heating rate of 10° C. / min.
[0030] Preferably, step (3) is specifically:
[0031] The amidoxime group-modified carbon nitride of step (1) and the carbon nitride containing nitrogen defects of step (2) are uniformly mixed, and then heated to 300-400° C. for 2-4 hours to perform a thermal polymerization reaction to obtain a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects;
[0032] Preferably, the high temperature reaction is carried out in a muffle furnace, more preferably, the temperature is increased to 325° C. at a heating rate of 10° C. / min.
[0033] In a second aspect, the present invention also provides a carbon nitride homojunction photocatalyst (CN x / ACN photocatalyst), which is prepared by the above-mentioned preparation method of carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects.
[0034] Preferably, two different carbon nitride homogeneities are combined, the carbon nitride modified by the amidoxime group is in the form of wrinkled flakes, the surface of the carbon nitride containing nitrogen defects is mostly porous, and the carbon nitride homogeneous junction is in the form of wrinkled scaly flakes and amorphous shapes.
[0035] In a third aspect, the present invention also provides the use of the above carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects in the visible light catalytic reduction removal of heavy metals, preferably the fixed removal of heavy metals in wastewater.
[0036] Removing heavy metals from wastewater preferably includes the following steps: uniformly mixing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects with the wastewater, oscillating and adsorbing under light-proof conditions, and after reaching adsorption equilibrium, performing photocatalytic reduction under a visible light source to complete the reduction and fixation of heavy metals in the wastewater.
[0037] Among them, the concentration of heavy metals in heavy metal wastewater is preferably 5 to 20 mg / L.
[0038] The shaking time is preferably 0 to 50 min.
[0039] The photocatalytic reduction fixation is preferably carried out under visible light with a wavelength of >420 nm.
[0040] The photocatalytic reduction fixation is preferably carried out under the condition that the pH of the heavy metal wastewater is 3.0 to 7.0.
[0041] The time for photocatalytic reduction fixation is preferably 40-120 min.
[0042] In the above application provided by the present invention, preferably, under the condition of 300W xenon lamp illumination, the time for removing heavy metals by visible light catalytic reduction is 5 to 120 minutes.
[0043] Preferably, the heavy metal is at least one of uranyl ion and hexavalent chromium.
[0044] Preferably, the dosage of the carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects is preferably 0.4-1.0 g / L, more preferably 0.5 g / L.
[0045] The present invention uses a low-cost carbon nitride precursor (such as urea) to prepare a carbon nitride having multiple active sites, strong adsorption performance for uranyl ions (U(VI)) and metallic chromium (Cr(VI)), green and stable, and highly responsive to visible light. x Carbon nitride homojunction (CN x / ACN) photocatalyst. Compared with the prior art, it has the following beneficial effects:
[0046] (1) The photocatalyst provided by the present invention is composed of carbon nitride containing amidoxime groups and nitrogen-containing defects (N x ) is a composite of carbon nitride. The amidoxime group has a strong adsorption property for U(VI) and can quickly capture U(VI); nitrogen defects (N x ) can induce an intermediate state gap and accelerate the migration efficiency of photogenerated carriers; the homojunction can delay the recombination of photogenerated carriers. The resulting photocatalyst has the characteristics of wide visible light absorption range, high absorption intensity, high photogenerated carrier conductivity, low recombination rate and high material stability.
[0047] (2) The present invention constructs two different carbon nitrides into a homojunction catalyst through a simple high-temperature calcination method, which not only improves the U(VI) capture performance, but also accelerates the separation and transfer efficiency of photogenerated carriers, thereby synergistically combining adsorption and photocatalysis to effectively improve the removal performance of uranium pollution in wastewater; the material is green and stable, the preparation method is simple, the raw materials are economical, the catalytic process does not produce any secondary pollution, and has certain environmental benefits.
[0048] (3) The raw material of the carbon nitride precursor of the present invention is urea, which is abundant in source, low in price, and the catalyst preparation method is simple, which is conducive to industrial-scale production.
[0049] (4) CN prepared by the present invention x / ACN photocatalyst has a certain adsorption capacity for U(VI), and also has the characteristics of generating and efficiently transferring photogenerated carriers under visible light radiation, which can reduce U(VI) in wastewater to U(IV) and fix it. It has the advantages of low material cost, good photocatalytic fixation effect, and fast treatment; the maximum reduction and fixation efficiency of the catalyst for U(VI) can reach 99.9%, and the reduction and fixation efficiency of U(VI) can still reach 74.2% after the reaction material is eluted and recycled for the third time, showing good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The N-containing x Carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN), amidoxime-modified carbon nitride (ACN), x Carbon nitride homojunction (CN x / ACN1,CN x / ACN2,CN x / ACN4 and CN x / ACN8) and X-ray diffraction patterns of pure carbon nitride (g-C3N4) photocatalysts prepared in Comparative Example 1.
[0051] Figure 2 The amidoxime group and N x Carbon nitride homojunction (CN x / ACN2) photocatalyst, with a magnification of 4000 times.
[0052] Figure 3 The N-containing x Carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN), amidoxime-modified carbon nitride (ACN), x Carbon nitride homojunction (CN x / ACN2) and Fourier transform infrared spectra of pure carbon nitride (g-C3N4) photocatalysts prepared in comparative example 1.
[0053] Figure 4 The N-containing x Carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN), amidoxime-modified carbon nitride (ACN), x Carbon nitride homojunction (CN x / ACN1,CN x / ACN2), and the UV-visible diffuse reflection absorption spectrum of the pure carbon nitride (g-C3N4) photocatalyst prepared in Comparative Example 1.
[0054] Figure 5 The N-containing x Carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN), containing amidoxime groups and N x Carbon nitride homojunction (CN x / ACN1,CN x / ACN2,CN x / ACN4,CN x / ACN8) and the pure carbon nitride (g-C3N4) photocatalyst prepared in comparative example 1 catalyzes the reduction and fixation of U(VI) in a visible light system.
[0055] Figure 6 For different amounts of amidoxime groups and N x The carbon nitride homojunction (CN in Example 1) x / ACN2) photocatalyst catalytic reduction and fixation of U(VI) in a visible light system.
[0056] Figure 7 The amidoxime group and N x The carbon nitride homojunction (CN in Example 1) x / ACN2) photocatalyst catalytic reduction and fixation of U(VI) under different pH conditions in a visible light system.
[0057] Figure 8 The amidoxime group and N x The carbon nitride homojunction (CN in Example 1) x / ACN2) photocatalyst cyclic catalytic reduction and fixation of U(VI). DETAILED DESCRIPTION
[0058] The technical solution of the present invention is clearly described in detail below in conjunction with specific implementation methods.
[0059] Example 1
[0060] A compound containing amidoxime group and N x A carbon nitride homojunction photocatalyst, the catalyst being prepared by the following method:
[0061] (1) 2 g of urea and 10 g of NaCl were mixed and then ground thoroughly. The mixture was placed in a muffle furnace and heated to 600 ° C at a rate of 5 ° C / min. The mixture was kept at 600 ° C for 2 h in a static air atmosphere and then cooled naturally to obtain cyanide-rich carbon nitride. 0.5 g of cyanide-rich carbon nitride was immersed in 30 mL of deionized water. 3.0 g of hydroxylamine hydrochloride (NH2OH·HCl) and 1.8 g of sodium hydroxide (NaOH) were added in sequence. After the mixture was dissolved, it was hydrothermally stirred at 80 ° C for 8 h at a stirring speed of 180 rpm. After centrifugal drying, amidoxime group-modified carbon nitride (ACN) was obtained.
[0062] (2) 10 g of urea was dissolved in 20 mL of a 0.25 g / L NaOH solution, and after being magnetically heated and stirred until completely dry, it was placed in a porcelain crucible with a lid, and heated to 600 °C at a rate of 10 °C / min in a muffle furnace, and maintained at 600 °C in a static air atmosphere for 2 h, and then naturally cooled to obtain nitrogen-deficient carbon nitride (CN x ).
[0063] (3) Take 0.25 g, 0.5 g, 1.0 g and 2.0 g of the amidoxime group-modified carbon nitride (ACN) prepared in step (1) and 2.0 g of the nitrogen-deficient carbon nitride (CN) prepared in step (2) respectively. x ) were mixed and ground, and the temperature was raised to 325°C at a rate of 10°C / min in a muffle furnace, and kept at 325°C in a static air atmosphere for 2 hours, and then naturally cooled to obtain amidoxime and defective carbon nitride homojunction photocatalyst (CN x / ACN), where CN in the composite homojunction x The mass ratio of ACN is denoted as CN x / ACN8、CN x / ACN4、CN x / ACN2 and CN x / ACN1.
[0064] Comparative Example 1
[0065] A preparation method of pure carbon nitride (g-C3N4) comprises the following steps:
[0066] 5 g of urea was placed in a covered porcelain crucible, and then placed in a muffle furnace and heated to 530°C at a rate of 5°C / min. The temperature was maintained at 530°C in a static air atmosphere for 2 hours and then naturally cooled to obtain a pure carbon nitride (g-C3N4) photocatalyst.
[0067] The nitrogen-containing defects (N x ) of carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN) and amidoxime-modified carbon nitride (ACN) x ) of carbon nitride homojunction (CN x / ACN1,,CN x / ACN2,CN x / ACN4 and CN x / ACN8), and the pure carbon nitride (g-C3N4) photocatalyst prepared in Comparative Example 1 were subjected to X-ray diffraction characterization analysis. The results are as follows Figure 1 As shown, g-C3N4 has diffraction peaks at 2θ=13.0° and 27.2°, which correspond to the (100) crystal plane of aromatic conjugation and the (002) crystal plane stacked between the planes of 3-s-triazine units in the graphite carbon nitride structure (JCPDS NO.50-1250). All samples in Example 1 maintain the characteristic lattice structure of g-C3N4, but after the grafting of the amidoxime group, the (100) crystal plane peak of ACN disappears, which may be due to the destruction of the ordered structure of the 3-s-triazine unit. At the same time, the diffraction peaks of ACN at 2θ=31.6°, 45.3°, 56.3° and 66.1° are respectively the (200), (220), (222) and (400) crystal planes in NaCl, which is related to the high-temperature molten salt calcination of ACN using NaCl as raw material. x The above diffraction peaks can be observed in the CN / CAN homojunction samples. x The (002) crystal plane strength of the / ACN samples is enhanced, which may be due to the reduction of the interlayer spacing of the homojunction. The above results indicate that x The two were successfully compounded with ACN to form a carbon nitride homojunction.
[0068] The amidoxime group and nitrogen defect (N x ) of carbon nitride homojunction (CN x / ACN2) photocatalyst was analyzed by transmission electron microscopy. Figure 2 As shown. Figure 2 It can be seen that the amidoxime group and N x Carbon nitride homojunction (CN x / ACN2) photocatalyst, CN x / ACN2 has a rough two-dimensional porous surface, and 2D g-C3N4 mostly presents irregular flakes. x The surface of carbon nitride is porous, and the amidoximized carbon nitride is in the form of wrinkled scaly flakes. xThe wrinkled ACN is tightly stacked together, making the material's microscopic surface have a certain thickness. x The transmission electron microscopy analysis results of / ACN2 are consistent with the X-ray diffraction characterization analysis results.
[0069] The N-containing x Carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN) and amidoxime-modified carbon nitride (ACN) x Carbon nitride homojunction (CN x / ACN2), and the pure carbon nitride (g-C3N4) photocatalyst prepared in Comparative Example 1 were subjected to Fourier transform infrared spectroscopy analysis. The results are as follows Figure 3 As shown. Figure 3 It can be seen that the wave number is between 3600-3000cm -1 The multi-peak group at 2175 cm-1 is mainly derived from the single-NH2 and adsorbed H2O molecules at the CN edge. -1 The obvious single peak at is related to the C≡N group of the two-dimensional carbon nitride, and this peak is x The sample disappears in the infrared spectrum with a wave number between 1700 and 1200 cm -1 Most of the peaks in the range come from the 3-s-triazine unit. In addition, the infrared spectrum of ACN at 931 cm -1 A new peak appeared at , indicating the presence of an ON bond, confirming the successful formation of the amidoxime group in the ACN sample. x / ACN2 samples also exist, indicating that CN x / ACN2 homojunction was successfully prepared. The weak peak is mainly due to the fact that ACN x The load on it is smaller.
[0070] The N-containing x Carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN), amidoxime-modified carbon nitride (ACN), x Carbon nitride homojunction (CN x / ACN1,CN x / ACN2), and the pure carbon nitride (g-C3N4) photocatalyst prepared in Comparative Example 1 were subjected to UV-visible diffuse reflection absorption spectroscopy analysis. The results are as follows Figure 4 As shown. Figure 4 It can be seen that pure g-C3N4 exhibits certain light absorption in both the ultraviolet and visible light regions, and the absorbance at 410nm is greatly reduced. x The light absorption intensity in the visible light region (400-450 nm) is slightly enhanced, and the absorbance curve of the amidoximated carbon nitride (ACN) is red-shifted, which indicates that Nx The introduction of and the grafting of amidoxime groups are beneficial to the energy absorption of the sample under visible light. x Absorbance curves of / ACN2 homojunction and g-C3N4 and CN x The difference between CN and x The absorbance of ACN1 decreased in the whole spectrum, which may be related to the x It is related to the composite mass ratio of ACN.
[0071] Example 2
[0072] The results of the experiments on the amidoxime groups and N x Effect of carbon nitride homojunction photocatalyst on the photocatalytic reduction and fixation of U(VI) in nuclear wastewater.
[0073] The nitrogen-containing defects (N x ) of carbon nitride (CN x ), amidoxime-modified carbon nitride (ACN), amidoxime-modified carbon nitride (ACN), amidoxime-modified carbon nitride (ACN), x ) of carbon nitride homojunction (CN x / ACN8,CN x / ACN4,CN x / ACN2,CN x / ACN1), and the pure carbon nitride (g-C3N4) photocatalyst prepared in Comparative Example 1, are applied to the photocatalytic reduction and fixation treatment of U(VI), and the steps are as follows:
[0074] The U(VI) stock solution was diluted to 10 mg / L with deionized water, and the initial pH value of the U(VI) solution was adjusted to 5.0 with 1.0 mol / L H2SO4 and NaOH solutions. 25 mg of CN in Example 1 were weighed separately. x / ACN8,CN x / ACN4,CN x / ACN2,CN x / ACN1, nitrogen-deficient carbon nitride (CN x), amidoxime-modified carbon nitride (ACN) photocatalyst and pure carbon nitride (g-C3N4) in comparative example 1 were added to a 50 mL U(VI) simulated wastewater solution with a concentration of 10 mg / L, and oscillated for 30 min under light-proof conditions to achieve adsorption equilibrium. Then, a visible light source was turned on and a photocatalytic reduction fixation reaction was carried out under its irradiation conditions (λ>420 nm). The reaction time was 120 min. During the reaction, samples were taken at 5 min, 10 min, 20 min, 40 min, 70 min and 120 min, respectively, and the solid-liquid separation was carried out through a 0.22 μm filter membrane. After the color development reaction was allowed to stand for 10 min, the concentration of the remaining U(VI) in the filtrate was determined at 578 nm using an ultraviolet spectrophotometer, and the residual rate of U(VI) was calculated. In this embodiment, a U(VI) solution with a volume of 50 mL and an initial concentration of 10 mg / L without any catalyst was set as a control group, and the residual rate of U(VI) was measured and calculated under the same conditions for blank comparison.
[0075] Different ACN doping ratios containing amidoxime groups and N x The reduction and fixation curve of U(VI) by the carbon nitride homojunction photocatalyst in the visible light system is shown in Figure 5 As shown. Figure 5 It can be seen that the reduction removal rate of U(VI) is very low under visible light alone, and almost no reduction reaction occurs. After 120 minutes of photocatalysis of pure g-C3N4 in the system, 76% of U(VI) remains, and the removal efficiency is 24%. Using ACN, CN x , CN x / ACN1,CN x / ACN2,CN x / ACN4, and CN x After 120 minutes of catalytic reduction of U(VI) by the / ACN8 heterogeneous catalyst in the photosystem, the residual rates of U(VI) in the system were 34.5%, 74.8%, 60.3%, 0.1%, 19.6% and 57.1%, respectively; the corresponding U(VI) fixation removal rates were 63.5%, 25.2%, 39.7%, 99.9%, 80.4% and 42.9%, respectively. This indicates that the loading of amidoxime groups and the construction of defective carbon nitride homojunctions can effectively promote the reduction and fixation of U(VI) contamination by carbon nitride materials in the visible system, among which CN x / ACN2 has the best effect.
[0076] Example 3
[0077] The presence of amidoxime groups and nitrogen defects (N x ) of carbon nitride homojunction (CN x / ACN2) photocatalyst solid-to-liquid ratio on the photocatalytic reduction and fixation of U(VI) in nuclear wastewater.
[0078] The amidoxime group and nitrogen defect (N x ) of carbon nitride homojunction (CN x / ACN2) photocatalyst is applied to the photocatalytic reduction and fixation of U(VI), and the steps are as follows:
[0079] The U(VI) stock solution was diluted to 10 mg / L with deionized water, and the initial pH value of the U(VI) solution was adjusted to 5.0 with 1.0 mol / L H2SO4 and NaOH solution. 10 mg, 25 mg, 40 mg, and 70 mg of CN in Example 1 were weighed respectively. x / ACN2 photocatalyst was added to a 50mL, 10mg / L U(VI) simulated wastewater solution, and oscillated for 60min under light-proof conditions to achieve adsorption equilibrium, then a visible light source was turned on and a photocatalytic reduction fixation reaction was carried out under its irradiation conditions (λ>420nm). The reaction time was 120min. During the reaction, the membrane was filtered for solid-liquid separation at 5min, 10min, 20min, 40min, 70min and 120min, respectively. After the color reaction was allowed to stand for 10min, the concentration of remaining U(VI) in the filtrate was determined by an ultraviolet spectrophotometer at 578nm, and the residual rate of U(VI) was calculated. CN with different catalyst dosages x The reduction and fixation curve of ACN2 to U(VI) in the visible light system is shown in the figure below: Figure 6 As shown. Figure 6 It can be seen that the use of 0.2g / L, 0.5g / L, 0.8g / L and 1.4g / L CN x After 120 minutes of catalytic reduction of U(VI) by / ACN2 photocatalyst in visible light system, the residual rates of U(VI) in the system were 75.4%, 0.1%, 15.1% and 28.1%, respectively; the corresponding U(VI) reduction removal rates were 24.6%, 99.9%, 84.9% and 71.9%, respectively. The reduction removal rate of U(VI) gradually increased with the increase of catalyst dosage. Generally speaking, the more catalysts, the more active sites, which promotes the removal of U(VI) in water. However, the continuous increase of dosage may reduce the light transmission effect in the system.
[0080] Example 4
[0081] Investigation of amidoxime groups and N x Carbon nitride homojunction (CN x / ACN2) photocatalyst at different pH values on the photocatalytic reduction and fixation of U(VI) in nuclear wastewater.
[0082] The amidoxime group and N prepared in Example 1 of the present invention x Carbon nitride homojunction (CN x / ACN2) photocatalyst was applied to the photocatalytic reduction and fixation treatment of U(VI), and the steps were as follows: dilute the U(VI) stock solution to a concentration of 10 mg / L with deionized water, and adjust the initial pH value of the U(VI) solution to 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0 and 10.0 with 1.0 mol / L H2SO4 and NaOH solutions. Take 25 mg of CN in Example 1 x / ACN2 photocatalyst was added to a 50mL, 10mg / L U(VI) simulated wastewater solution, and oscillated for 30min under light-proof conditions to achieve adsorption equilibrium, then a visible light source was turned on and a photocatalytic reduction fixation reaction was carried out under its irradiation conditions (λ>420nm). The reaction time was 120min. During the reaction, the filter membrane was used for solid-liquid separation at 5min, 10min, 20min, 40min, 70min and 120min, respectively. After the color reaction was allowed to stand for 10min, the concentration of the remaining U(VI) in the filtrate was determined by an ultraviolet spectrophotometer at 578nm, and the residual rate of U(VI) was calculated. CN under different pH conditions x The reduction and fixation curve of ACN2 to U(VI) in the visible light system is shown in the figure below: Figure 7 As shown. Figure 7 It can be seen that when the pH in the system is 3.0, 4.0, 5.0, 6.0, 7.0, 8.0 and 9.0 respectively, CN x After 120 min of catalytic reduction of U(VI) by / ACN2 in a visible light system, the residual rates of U(VI) in the system were 98.4%, 34.6%, 0.1%, 39.1%, 50.3%, 75.9%, 90.8% and 99.4%, respectively. The corresponding U(VI) reduction removal efficiencies were 1.6%, 65.4%, 99.9%, 60.9%, 49.7%, 24.1%, 9.2% and 0.6%, respectively. The results showed that the U(VI) reduction removal rate increased when the solution pH value increased from 3.0 to 5.0, but when the pH was further increased to neutral and alkaline, the U(VI) reduction removal efficiency decreased.
[0083] Example 5
[0084] Investigation of amidoxime groups and N x Carbon nitride homojunction (CN x / ACN2) photocatalyst stability.
[0085] The amidoxime group and N prepared in Example 1 of the present invention x Carbon nitride homojunction (CN x / ACN2) photocatalyst was used for the photocatalytic reduction and fixation of U(VI), and the steps were as follows: the U(VI) stock solution was diluted to 10 mg / L with deionized water, and the initial pH value of the U(VI) solution was adjusted to 5.0 with 1.0 mol / L H2SO4 and NaOH solution. 25 mg of CN in Example 1 was weighed x / ACN-2 photocatalyst was added to a 50 mL U(VI) simulated wastewater solution with a concentration of 10 mg / L. The solution was shaken for 30 min in a dark environment to achieve adsorption equilibrium. Then, a visible light source was turned on and a photocatalytic reduction fixation reaction was carried out under the irradiation conditions (λ>420 nm). The reaction time was 120 min. x The / ACN2 catalyst was collected by centrifugation, soaked in 0.1 mol / L NaHCO3 solution for 30 min, washed twice with deionized water, and dried in vacuum at 65 °C. x The / ACN2 catalyst was taken out and the U(VI) photocatalytic experiment was repeated under the same catalytic reduction conditions as the first time and CN was regenerated according to the same method. x / ACN2. This process was repeated 4 times. The residual solution after the photocatalytic reduction of U(VI) was completely centrifuged, and after the color reaction was allowed to stand for 10 minutes, the concentration of the remaining U(VI) was measured at 578 nm using an ultraviolet spectrophotometer to calculate the CN of the composite photocatalytic material. x / ACN2 cyclic photocatalytic reduction fixed U(VI) residual rate, the results are as follows Figure 8 As shown. Figure 8 It can be seen that the CN prepared by the present invention x After the third and fourth photocatalytic cycles, the visible light photocatalytic removal effect of the ACN2 photocatalyst on U(VI) can still reach 74.2% and 63.8%, respectively. This shows that the photocatalytic removal effect of the ACN2 photocatalyst containing amidoxime groups and N x The carbon nitride homojunction photocatalyst has good stability and the catalyst has a certain regeneration and reuse effect.
[0086] In summary, the present invention effectively utilizes urea, which is economical and has abundant raw materials, as a carbon nitride precursor to obtain a carbon nitride containing nitrogen defects (N x ) of carbon nitride (CN x ) and amidoxime-modified carbon nitride (ACN), and then the two are thermally polymerized by a simple high-temperature calcination method to obtain amidoxime-modified carbon nitride (ACN) with multiple active sites, strong U(VI) adsorption performance, and high photosensitivity response intensity. x ) carbon nitride homojunction photocatalyst. The catalyst has a simple preparation process, no secondary pollution, good environmental benefits, high removal efficiency of uranyl ions in wastewater, and simple operation of the catalytic reduction process. The present invention is of great significance to the development of efficient carbon nitride-based multiphase U (VI) photocatalysts.
[0087] The above are only preferred specific implementations of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and improved concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects, characterized in that: The steps include: Step (1), after the carbon nitride precursor and the sodium salt are mixed and ground evenly, the amidoxime group-modified carbon nitride is obtained by a high-temperature molten salt method; Step (2), subjecting the carbon nitride precursor to a high temperature alkali etching method to obtain carbon nitride containing nitrogen defects; Step (3), mixing the amidoxime group-modified carbon nitride of step (1) and the carbon nitride containing nitrogen defects of step (2) in a mass ratio of 1:2, and then calcining them at high temperature to cause thermal polymerization between the two, and finally obtaining a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects.
2. The method for preparing the carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects according to claim 1, characterized in that: Step (1) is specifically as follows: The carbon nitride precursor and the sodium salt are mixed and ground evenly, placed in a porcelain crucible, calcined at 500-700°C for 1-3 hours, cooled to obtain cyanide-rich carbon nitride, added to water, and then added with hydroxylamine hydrochloride and alkaline substances to obtain a mixed solution, stirred hydrothermally at high temperature, centrifuged and dried to obtain amidoxime group-modified carbon nitride; Preferably, the carbon nitride precursor is urea; Preferably, the sodium salt is sodium chloride, more preferably, the sodium salt is added in the form of sodium chloride crystals, and most preferably, the mass ratio of sodium chloride to urea is preferably (1.0-5.0):1; Preferably, the calcination is carried out in a muffle furnace, more preferably, the temperature is increased to 530° C. at a heating rate of 10° C. / min; Preferably, the water level is deionized water, more preferably, the mass ratio of cyanide-rich carbon nitride to deionized water is 1:(50-80), and the mass ratio of cyanide-rich carbon nitride to hydroxylamine hydrochloride is 1:(5.0-8.0); Preferably, the alkaline substance is sodium hydroxide, more preferably, the sodium hydroxide is added in the form of solid particles, and most preferably, the concentration of sodium hydroxide in the aqueous solution is preferably 0.03 to 0.1 g / mL; Preferably, the high temperature is 70-80°C; Preferably, the stirring method is magnetic stirring, and more preferably, the magnetic stirring speed is 200 to 300 rpm; Preferably, the centrifugation condition is: centrifugation at a rotation speed of 6000-8000 rpm for 15-20 min.
3. The method for preparing the carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects according to claim 1, characterized in that: Step (2) is specifically as follows: The carbon nitride precursor is dissolved in an alkaline solution, heated and stirred until completely dry, and the mixture is placed in a covered porcelain crucible, calcined at 500-700°C for 2-6 hours, and cooled to obtain carbon nitride containing nitrogen defects; Preferably, the carbon nitride precursor is urea, and more preferably, the mass ratio of the carbon nitride precursor to the alkaline substance in the alkaline solution is (1800-2400):1; Preferably, the alkaline solution is a KOH solution, and more preferably, the concentration of the alkaline solution is 0.2 to 0.4 g / L; Preferably, the stirring method is magnetic stirring, more preferably, the stirring speed is 200 to 300 rpm, and the stirring time is 15 to 20 h; Preferably, the heating temperature is 50-70°C; Preferably, the calcination is carried out in a muffle furnace, more preferably, the temperature is increased to 520° C. at a heating rate of 10° C. / min.
4. The method for preparing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects according to any one of claims 1 to 3, characterized in that: Step (3) is specifically as follows: The amidoxime group-modified carbon nitride of step (1) and the carbon nitride containing nitrogen defects of step (2) are uniformly mixed, and then heated to 300-400° C. for 2-4 hours to perform a thermal polymerization reaction to obtain a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects; Preferably, the high temperature reaction is carried out in a muffle furnace, more preferably, the temperature is increased to 325° C. at a heating rate of 10° C. / min.
5. A carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects, characterized in that: The photocatalyst is prepared by the method for preparing a carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects as described in any one of claims 1 to 4.
6. The carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects according to claim 1, characterized in that: It is composed of two different carbon nitride homogeneities. The carbon nitride modified with amidoxime groups is in the form of wrinkled flakes, and the surface of the carbon nitride containing nitrogen defects is mostly porous. The carbon nitride homogeneous junction is in the form of wrinkled scaly flakes and amorphous shapes.
7. Use of the carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects as claimed in claim 5 or 6 in the removal of heavy metals by visible light catalytic reduction.
8. The use according to claim 7, characterized in that: Under the illumination of a 300W xenon lamp, the time for removing heavy metals by visible light catalytic reduction is 5 to 120 minutes.
9. The use according to claim 7, characterized in that: The heavy metal is at least one of uranyl ion and hexavalent chromium.
10. The use according to any one of claims 7 to 9, characterized in that: The dosage of the carbon nitride homojunction photocatalyst containing amidoxime groups and nitrogen defects is 0.5 g / L.